The study of left ventricular relaxation and filling abnormalities in acute coronary syndrome by doppler echocardiography - Biradar, Siddanagouda M; Holyachi, Renuka; Badiger, Sharan; Biradar, Mallanagouda S; Balaganur, S G (Recent Research in Science and Technology, 2013)
Objectives: To study the left ventricular relaxation and filling abnormalities by doppler echocardiography and prognosis of acute coronary syndrome. Methods: Fifty patients of acute coronary syndrome were included in the study. The left ventricular diastolic dysfunction was studied using doppler transmitral velocities within the apical 4- chambers view (1st study-on the day of admission and 2nd study- after one week). The various parameters studied were peak E (peak rapid filling velocity), peak A (atrial contraction wave), E/A ratio, E-DT (E- deceleration time), IVRT (isovolumetric relaxation time), S-wave (systolic forward flow wave), D-wave (diastolic forward flow wave) and AR-wave (atrial reversal wave). Results: Of 50 patients studied 3 had normal, 36 patients had impaired relaxation, 5 patients had pseudo-normalization, 4 patients reversible and 2 patients irreversible restrictive filling on the day of admission (1st study). In the 2nd study (after one week) 16 were normal, 20 patients had impaired relaxation, 5 patients had pseudo-normalization, 6 patients had reversible and 2 patients had irreversible restrictive filling. Conclusion: Doppler echocardiographic assessment of left ventricular diastolic dysfunction in the setting of acute coronary syndrome helps in the management and provides independent noninvasive prognostic information.